Enabling Teams to Implement Innovative Personalized Activation in a Public Sector Context: Why and How Frontline Leadership Matters - Mbatudde Skjold, Suzan; Munkejord, Mai Camilla (Scandinavian Journal of Public Administration, 2023)
This article investigates the strategies used by frontline supervisors to lead teams in the implementation of innovative activation services and the ways in which these strategies are perceived by the frontline workers they lead. Empirical data are collected from team observations and in-depth interviews with frontline supervisors and workers known as employment specialists in a public sector context, i.e., in the Norwegian Labour and Welfare Administration (NAV). In this context,a large-scale programme known as Extended Follow-Up was implemented beginning in 2017 with the aim of improving activation services for persons with complex support needs. We identified two leadership strategies: a) a team-focused strategy based on interdependence, in which frontline workers were encouraged to shape and adapt the activation services to each jobseeker, and b) a rule-focused strategy based on constant monitoring of frontline workers to secure their adherence to predefined tools and aims. The former strategy promoted team cohesion and provided the necessary psychological safety to implement the personalized activation service,while the latter strategy limited the frontline workers’ creativity and room to manoeuvre. Our findings reveal that integrative leadership approaches that combine autonomy with support present greater prospects for successful innovation implementation in a public sector context.